2008
DOI: 10.1016/j.juro.2008.01.086
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Dysfunction in Rats With Metabolic Syndrome Induced by Long-Term Fructose Feeding

Abstract: Our data show that a significant proportion of fructose fed rats show time related alterations in bladder biochemical, morphological and functional properties. The proinflammation and myopathy of the bladder induced by metabolic perturbations have important roles in causing bladder dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 20 publications
3
59
1
Order By: Relevance
“…Associations between intensity of male LUTS and presence of the metabolic syndrome were also observed from the Boston Area Community Health (BACH) Survey (Kupelian et al 2009). In line with these clinical findings, bladder dysfunction has also been reported in rat models of metabolic syndrome (Chung et al 2013;Lee et al 2008). In line with others (Bunn et al 2015;Kirby et al 2010), we conclude that metabolic syndrome apparently exhibits a more robust association with LUTS than its individual components of dyslipidemia and diabetes.…”
Section: Clinical Associations Between Atherosclerosis Risk Factors Asupporting
confidence: 54%
“…Associations between intensity of male LUTS and presence of the metabolic syndrome were also observed from the Boston Area Community Health (BACH) Survey (Kupelian et al 2009). In line with these clinical findings, bladder dysfunction has also been reported in rat models of metabolic syndrome (Chung et al 2013;Lee et al 2008). In line with others (Bunn et al 2015;Kirby et al 2010), we conclude that metabolic syndrome apparently exhibits a more robust association with LUTS than its individual components of dyslipidemia and diabetes.…”
Section: Clinical Associations Between Atherosclerosis Risk Factors Asupporting
confidence: 54%
“…This may be another molecular base of OAB in MtS, in rats. Lee et al showed structural changes of cells, in MtS, in another experimental study [21]. In a recent study, Millagro et al reported genetic and molecular base of MtS in women with MtS [22].…”
Section: Discussionmentioning
confidence: 95%
“…It has been accepted that MtS occurs on the basis of insulin resistance (IR) [4]. Thus, endothelial injury may come into question, and this may lead to atherosclerosis which may cause to decrease blood supply of bladder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionally, there was less contractile activity of the bladder strip to potassium chloride (KCl) in vitro. 25 The authors of the study also observed that mitochondria in bladder smooth muscle cell were denatured , which lead to the idea that oxidative stress existed. These notions support our hypothesis that oxidation-dependent AGE was accumulated in bladder with oxidative stress, which leads inflammatory cells infiltration and accelerates bladder dysfunction.…”
Section: Discussionmentioning
confidence: 97%